Ethnicity based variation in expression of E-cadherin in patients with squamous cell carcinoma of the oral tongue - Sgaramella, Nicola; Wilms, Torben; Boldrup, Linda; Loljung, Lotta; Gu, Xiaolian; Coates, Philip J; Hassellöf, Petra; Califano, Luigi; Lo Muzio, Lorenzo; Fåhraeus, Robin; Norberg Spaak, Lena; Franco, Renato; et al. (Oncology letters, 2018)
The oral tongue is the most common site for tumours within the oral cavity. Despite intense research, there has been no improvement in the survival rate for patients with oral tongue squamous cell carcinoma (OTSCC) during the last decades. Differences between oral cancer patients based on ethno-geographical distribution have been reported. The present study used immunohistochemistry to evaluate commonly used markers of cancer cell phenotypes, E-cadherin, β-catenin and cytokeratins 5 and 19, in 120 patients with OTSCC. To evaluate the impact of ethnicity, patients from Sweden and Italy were included. A higher proportion of Swedish patients exhibited high expression of E-cadherin in their tumours (P=0.039), and high levels of E-cadherin in Swedish OTSCC patients that had succumbed to their disease were associated with poor prognosis. These data demonstrated differences in the pathological characteristics of OTSCC between two different European populations. The findings emphasise the need to take ethnicity/geographical location of patients into account when comparing results from different studies of OTSCC.
Keywords: squamous cell carcinoma; E-cadherin; beta catenin; oral tongue; ethnicity